Interpolation in Normal Extensions of the Brouwer Logic - Kostrzycka, Zofia (Bulletin of the Section of Logic, 2016)
The Craig interpolation property and interpolation property for deducibility are considered for special kind of normal extensions of the Brouwer logic.